1993
DOI: 10.1002/j.1460-2075.1993.tb06097.x
|View full text |Cite
|
Sign up to set email alerts
|

DnaK, DnaJ and GrpE form a cellular chaperone machinery capable of repairing heat-induced protein damage.

Abstract: Members of the conserved Hsp70 chaperone family are assumed to constitute a main cellular system for the prevention and the amelioration of stress‐induced protein damage, though little direct evidence exists for this function. We investigated the roles of the DnaK (Hsp70), DnaJ and GrpE chaperones of Escherichia coli in prevention and repair of thermally induced protein damage using firefly luciferase as a test substrate. In vivo, luciferase was rapidly inactivated at 42 degrees C, but was efficiently reactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
484
3
6

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(531 citation statements)
references
References 45 publications
32
484
3
6
Order By: Relevance
“…Hsp70 members are highly multifunctional proteins that have been shown to play a key role in proteome maintenance, such as in de novo protein folding (co-or post-translational), protein translocation across membranes (Lyman and Schekman, 1997;Matlack et al, 1999;Young et al, 2003), refolding of stress damaged proteins (Ben-Zvi et al, 2004;Schroder et al, 1993;Sharma et al, 2010), in preventing protein aggregation (Auluck et al, 2002;Broadley and Hartl, 2009;Klucken et al, 2004;Sakahira et al, 2002;Warrick et al, 1999), disaggregation (Ben-Zvi and Goloubinoff, 2001;Diamant et al, 2000;Liberek et al, 2008;Shorter, 2011) and degradation of irreparable misfolded proteins (Bercovich et al, 1997;Fisher et al, 1997;Urushitani et al, 2004). These essential and diverse cellular functions of Hsp70 are attributed to its physical interaction with various co-chaperones such as Hsp40, NEFs and with proteins such as HIP, HOP and CHIP.…”
Section: Ii41121 the Hsp70 Chaperone Systemmentioning
confidence: 99%
“…Hsp70 members are highly multifunctional proteins that have been shown to play a key role in proteome maintenance, such as in de novo protein folding (co-or post-translational), protein translocation across membranes (Lyman and Schekman, 1997;Matlack et al, 1999;Young et al, 2003), refolding of stress damaged proteins (Ben-Zvi et al, 2004;Schroder et al, 1993;Sharma et al, 2010), in preventing protein aggregation (Auluck et al, 2002;Broadley and Hartl, 2009;Klucken et al, 2004;Sakahira et al, 2002;Warrick et al, 1999), disaggregation (Ben-Zvi and Goloubinoff, 2001;Diamant et al, 2000;Liberek et al, 2008;Shorter, 2011) and degradation of irreparable misfolded proteins (Bercovich et al, 1997;Fisher et al, 1997;Urushitani et al, 2004). These essential and diverse cellular functions of Hsp70 are attributed to its physical interaction with various co-chaperones such as Hsp40, NEFs and with proteins such as HIP, HOP and CHIP.…”
Section: Ii41121 the Hsp70 Chaperone Systemmentioning
confidence: 99%
“…The most important members of the Hsp70 family are the constitutive cytosolic Hsc70 (Hsp73), the inducible cytosolic Hsp70 (Hsp72), the Bip (Grp78) localized in the endoplasmic reticulum, the mHsp70 (Grp75, mortalin [24]) localized in the mitochondria, and the several bacterial homologues such as DnaK (in E. coli). By using ATP, and working in concert with other chaperones and co-chaperones, the members of the Hsp70-family take part in nearly all of the typical intracellular chaperone functions, including protein folding [21,22,30,38], refolding of damaged proteins [68], inhibition of aggregation [30,38], resolubilization of aggregated proteins [73], the transport of several proteins [30,38], and the control of several signal transduction pathways [9,60], including the induction of senescence [24]. Furthermore, Hsp70 proteins are also involved in many processes outside the cell, including cytoprotection [36,37,41], cytokine-releasing effects, and the modulation of various immune functions [39,51,53,54,64,65,72,76,84].…”
Section: Members Of the Hsp70 Molecular Chaperone Familymentioning
confidence: 99%
“…antibodies) and the surrounding cells, leading to tissue damage. Hsp70 may play a crucial role in defending these important molecules and tissues under these conditions by increasing the resistance of the cells against extracellular toxins [41], and decreasing the apoptotic and necrotic liability of the cells [36], and also because of its protein repair character (refolding ability) [68], the prevention of protein aggregation [30,38], and resolubilization of such aggregates [73].…”
Section: The Possible Defense Functions Of Salivary Hsp70 In Mucosal mentioning
confidence: 99%
“…Such proteins must necessarily depart the chaperonin, or they would engorge GroEL. In an in vitro model of this situation, using a nonhomologous substrate, Bukau and coworkers have shown that the monomeric protein, luciferase, is bound efficiently by GroEL, but cannot be released from it productively (Schroder et al, 1993). On the other hand, they observed that the E. coli Hsp70 system, DnaK-DnaJ-GrpE, can direct the protein to native form.…”
Section: E Release Of Non-native Polypeptides During the Groel-groes mentioning
confidence: 99%